Partial epilepsy: A pictorial review of 3 TESLA magnetic resonance imaging features (Clinics, 2015)
Epilepsy is a disease with serious consequences for patients and society. In many cases seizures are sufficiently disabling to justify surgical evaluation. In this context, Magnetic Resonance Imaging (MRI) is one of the most valuable tools for the preoperative localization of epileptogenic foci. Because these lesions show a large variety of presentations (including subtle imaging characteristics), their analysis requires careful and systematic interpretation of MRI data. Several studies have shown that 3 Tesla (T) MRI provides a better image quality than 1.5 T MRI regarding the detection and characterization of structural lesions, indicating that high-field-strength imaging should be considered for patients with intractable epilepsy who might benefit from surgery. Likewise, advanced MRI postprocessing and quantitative analysis techniques such as thickness and volume measurements of cortical gray matter have emerged and in the near future, these techniques will routinely enable more precise evaluations of such patients. Finally, the familiarity with radiologic findings of the potential epileptogenic substrates in association with combined use of higher field strengths (3 T, 7 T, and greater) and new quantitative analytical post-processing techniques will lead to improvements regarding the clinical imaging of these patients. We present a pictorial review of the major pathologies related to partial epilepsy, highlighting the key findings of 3 T MRI.